The Causal Effect of Firm Productivity on Climate Change: Evidence from the MENA Region - El Azhary, Shahd (AUC Knowledge Fountain, 2023)
The relationship between firm productivity and climate change matters importantly to sustainable growth goals. The MENA region is very vulnerable to desertification because of an increase in temperature. The purpose of this study is to assess the productivity of firms, by sector, on climate change through a panel VAR (PVAR) model to investigate firms’ total factor productivity (TFP) on temperature increases on the region. The positive relationship between both variables for most sectors, except for the financial and basic materials sectors, demonstrates the need for policy makers to formulate harsher regulations against climate change.